2017
DOI: 10.1111/ceo.13065
|View full text |Cite
|
Sign up to set email alerts
|

Design and methodology of the Shanghai child and adolescent large‐scale eye study (SCALE)

Abstract: ImportanceNearly half of children suffering vision impairment reside in China with myopia accounting for the vast majority.BackgroundTo describe the design and methodology of the Shanghai Child and Adolescent Large‐scale Eye Study (SCALE).DesignThe SCALE was a city wide, school‐based, prospective survey.ParticipantsChildren and adolescents aged 4–14 years from kindergarten (middle and senior), primary schools and junior high schools of all 17 districts and counties of the city of Shanghai, China were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…The SCALE‐HM study is a population‐based, prospective, examiner‐masked study. The database of the SCALE study (the methodology of which has been published elsewhere) (He et al 2018 ) will be used to select children and adolescents, aged between 4 and 18 years, with high myopia for participation in the study. The trial protocol was approved by the Shanghai General Hospital Ethics committee and adhered to the tenets of the Declaration of Helsinki (ClinicalTrials.gov Identifier: NCT03666052).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCALE‐HM study is a population‐based, prospective, examiner‐masked study. The database of the SCALE study (the methodology of which has been published elsewhere) (He et al 2018 ) will be used to select children and adolescents, aged between 4 and 18 years, with high myopia for participation in the study. The trial protocol was approved by the Shanghai General Hospital Ethics committee and adhered to the tenets of the Declaration of Helsinki (ClinicalTrials.gov Identifier: NCT03666052).…”
Section: Methodsmentioning
confidence: 99%
“…Based on a large‐scale eye study involving more than 2 million children and adolescents (He et al 2018 ), the aim of the present study was to conduct a long‐term prospective study for further exploration of the fundus changes, as well as the accompanying visual functional changes in children with high myopia. Susceptibility genes related to high myopia and myopic fundus changes were also tested to elucidate the mechanisms behind these changes.…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the longitudinal trends consequently to get a clear knowledge of the eye care needs is the key point to prevent irreversible blindness in Children [4]. Many childhood cohort studies have reported the accurate observation of eye disease progression and provided precious clues for prevention and treatment needs among children, such as the Singapore Cohort Study of the Risk Factors for Myopia, the Orinda Longitudinal Study of Myopia, the Anyang Childhood Eye Study (ACES) and so on [5][6][7][8][9]. To our knowledge, there is a lack of longitudinal investigation on eye diseases of school-age children in the Tibetan plateau in China.…”
Section: Introductionmentioning
confidence: 99%
“…Then based on the proportion of students in these two stratums (ie, 29% in urban and 71% in sub-urban, 2014 Shanghai statistics), two urban and six sub-urban districts (eight clusters) were randomly selected. Using previously gathered information on ocular health of all students from the 940 government primary schools in these 16 districts, 12 schools with similar prevalence of visual impairment (uncorrected visual acuity in right eye ≤20/25) and myopia (non-cycloplegic spherical equivalent (SE) ≤ −1.00D) in each district were grouped. Three schools were randomly chosen from each selected district and randomly assigned to test I, test II or control groups.…”
Section: Intervention Sample Size and Randomizationmentioning
confidence: 99%